Coğrafya öğretmeni kimdir? - KOCALAR, ALİ OSMAN (My University, 2023)
Öğrencilerin algılarını ölçmek amacıyla son yıllarda yapılan metafor çalışmalarının arttığı görülmektedir. Bu açıdan üniversite düzeyinde eğitim alan öğrencilerin coğrafya derslerini vermekle görevli olan coğrafya öğretmenleri hakkında oluşturdukları metaforlar büyük öneme sahiptir. Bu çalışma, üniversite öğrencilerinin “coğrafya öğretmeni” kavramına yönelik algılarının araştırılması amacıyla gerçekleştirilmiştir. Araştırmaya 5 farklı bölümden toplam 138 öğrenci katılmıştır. Araştırmaya katılan üniversite öğrencilerinden, araştırmacı tarafından hazırlamış ve iki kısımdan oluşan formu doldurmaları istenmiştir. İlk kısımda kişisel bilgileri içeren bölüm yer alırken ikinci kısımda coğrafya öğretmeni kavramına ilişkin sahip oldukları zihinsel imgeleri ortaya çıkarmak amacıyla hazırlanmış olan «Coğrafya öğretmeni... gibidir; çünkü …” cümlesindeki boşlukların tamamlaması istenmiştir. Araştırma ile elde edilen verilerin Excel ortamında anlamsal ve sayısal analizi sonucunda 5 kategori oluşturulmuştur. Bunlar; coğrafya alanı veya terimi, bilgi ve öğreticilik, meslek, rehber ve araştırmacı-yorumlayıcı şeklindedir. Araştırma sonucunda öğrencilerin en fazla harita ve dünya ile ilgili metaforlar geliştirdiği görülmüştür. Ayrıca kategoriler içinde en fazla metafor, coğrafya alanı veya bir coğrafya terimi ile olduğu sonucuna varılmıştır. Bunun yanında coğrafya öğretmenleri için bilgi ve bilgelikle bağlantılı metaforların önemli oranda olduğu görülmüştür.

In recent years, it is seen that metaphor studies aimed at measuring students’ perceptions have increased. In this respect, the metaphors created by university students about geography teachers who are responsible for teaching geography lessons, are of great importance. This study was conducted to investigate the perceptions of university students towards the concept of “geography teacher”. A total of 138 students from 5 different departments participated in the study. The university students participating in the study were asked to fill out the form consisting of two parts prepared by the researcher. In the first part, there was a section containing personal information, while in the second part, the participants were asked to complete (fill in) the blanks in the sentences like “Geography teacher is like... because...”, which was prepared to reveal the mental images they had about (have regarding) the concept of geography teacher. According to the data obtained as a result of the research, 5 categories were created in the semantic and numerical analysis report in the Excel environment. These are; geography field or term, knowledge and teaching, profession, guide and researcher-interpretive. As a result of the research, it was seen that students mostly developed maps and metaphors about the world. In addition, it was concluded that the most metaphors among the categories were with the field of geography or a geography term. Additively, it has been seen that metaphors related to knowledge and wisdom are important considerablely amount for geography teachers. In addition, it has been seen that metaphors related to knowledge and wisdom were found to be significant for geography teachers.
Keywords: Metafor; coğrafya öğretmeni; üniversite öğrencisi; kavram; Metaphor; geography teacher; university student; concept